Clonal hierarchy of main molecular lesions in acute myeloid leukaemia - Herudkova, Zdenka; Culen, Martin; Folta, Adam; Jeziskova, Ivana; Cerna, Jana; Loja, Tomas; Tom, Nikola; Smejkal, Jiri; Semerad, Lukas; Dvorakova, Dana; Mayer, Jiri; Racil, Zdenek (British journal of haematology, 2020)
Genetic mutations in acute myeloid leukaemia (AML) are assumed to occur in a sequential order; however, the predominant hierarchical roles of specific mutated genes have not been fully described. In this study, we aimed to determine the clonal involvement of the most frequent AML-associated mutations. Using a targeted sequencing panel for 18 genes, we traced changes and relative clonal contribution of mutations in 52 patients. We analysed 35 pairs of diagnosis and relapse samples, 27 pairs of primary samples and corresponding patient-derived xenografts, and 34 pairs of total leukocytes and corresponding isolated primitive cells or blast populations. In both relapse and xenografts, we observed conservation of main leukaemic clones and variability was limited to subclones with late-acquired mutations. AML evolution thus mainly involved modification of subclones while the clonal background remained unchanged. NPM1 mutations were identified as the most probable leukaemia-transformation lesion, remaining conserved in contrast to high variation of accompanying subclonal FLT3 and NRAS mutations. DNMT3A mutations represented the most stable mutations forming a preleukaemic background in most samples. Mutations in genes IDH1/2, TET2, RUNX1, ASXL1 and U2AF1 were detected both as preleukaemic and as subclonal lesions, suggesting a non-specific order of acquisition.
Keywords: transplantace nádorů; Young Adult; kombinovaná terapie; Recurrence; nádorové proteiny; Clone Cells; Male; mutace; Combined Modality Therapy; acute myeloid leukaemia; Neoplastic Stem Cells; Antineoplastic Combined Chemotherapy Protocols; mladý dospělý; Neoplasm Transplantation; heterografty; Adult; transplantace hematopoetických kmenových buněk; akutní myeloidní leukemie; Aged; dospělí; mužské pohlaví; senioři; recidiva; klonální evoluce; mutations; patient-derived xenograft; leukocyty; myši inbrední NOD; buněčné klony; Nucleophosmin; Animals; clonality; lidé; Leukemia, Myeloid, Acute; ženské pohlaví; Humans; zvířata; Clonal Evolution; Leukocytes; protokoly protinádorové kombinované chemoterapie; Heterografts; myši; Neoplasm Proteins; Genes, Neoplasm; Mutation; nádorové kmenové buňky; Mice; Female; Mice, Inbred NOD; relapse; nukleofosmin; lidé středního věku; geny nádorové; Hematopoietic Stem Cell Transplantation; Middle Aged